Impact of endurance training on vo₂max, sprint ability, and lactate in youth female basketball players - Pruchya Chumvangvapee; Pimonpan Taweekarn Vannajak; Kunavut Vannajak; Yupaporn Kanpetta; Wareerat Kokittipong; Piyawat Luesopha (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Basketball is an increasingly popular sport characterized by rapid movements and frequent positional changes. These movements demand high speed and stamina, with players exhibiting exertion levels comparable to short-distance sprinters. To meet the physiological demands of the sport, athletes require enhanced aerobic capacity, sprinting ability, and lactate regulation.